UPAYA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DALAM MENERAPKAN PROSES PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK MELALUI SUPERVISI KUNJUNGAN KELAS DI SMPN 18 DUMAI - Edy Ahmad (Jurnal PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the 2013 curriculum that requires learning that is able to improve student competence in aspects of knowledge, skills and attitudes. The purpose of this study is to increase the pedagogical competence of teachers in applying scientific approach based learning through supervision of class visits. This research was conducted at 18 Dumai Public Middle School starting February 11 to March 30, 2019. The method used is Class Action Research. The subjects of this study were 8 science teachers in the field of science and mathematics. Research data in the form of documents, observation sheets, and interviews. Data were analyzed through 3 steps, namely: data reduction, data exposure, and conclusions. The results of this study conclude that the supervision of class visits can improve the pedagogical competence of teachers in applying the learning process based on the scientific approach at Dumai 18 Public Middle School. The percentage of teacher pedagogic competence in the first cycle was 55%, which included the less category increased in the second cycle to 79% in the good category.